Research and design of multi-tenant scheme for Kubernetes container cloud platform - Danchi HUANG; Zhenwei HE; Liyun YAN; Yuanzhi LIN; Xinzhang YANG (Dianxin kexue)
In the container cloud platform,tenants share the underlying computing,storage,network and other resources,and there are problems with the operation of the tenant container and data security.Based on the analysis of Kubernetes scheme based on access control and resource isolation,a multi-tenant cloud platform was proposed,which covers multi-tenancy management model,multi-tenant access control,computing resources isolated and network resources,etc.The proposed model can be practically improving resource isolation capability based on containers of Kubernetes cloud platform,effectively reduce the data security hidden danger.